The role of three-dimensional power Doppler ultrasound parameters measured on hCG day in the prediction of pregnancy during in vitro fertilization treatment. (August 2016) - Zhang, Tianjie; He, Yaqiong; Wang, Yuan; Zhu, Qingling; Yang, Jing; Zhao, Xiaoming; Sun, Yun
Abstract: Objective: To investigate the value of ultrasound for the assessment of endometrial receptivity during in vitro fertilization (IVF) and embryo transfer (ET). Materials and methods: Only those patients in their first IVF cycle, followed a standard long gonadotropin releasing hormone (GnRH) agonist long ovarian stimulation regimen, and had 2 highest scoring embryos transferred on day 3 were included in the study. A 3D ultrasound examination was performed on the day of human chorionic gonadotropin (hCG) injection to determine endometrial thickness, endometrial pattern, peak systolic velocity (PSV), end diastolic velocity (EDV), pulsatility index (PI) and resistance index (RI) of endometrial spiral arteries, endometrial volume, vascularization index (VI), flow index (FI) and vasculariztion flow index (VFI) of endometrial and subendometrial region. Analyses were carried on between pregnant and non-pregnant groups, and miscarriage and ongoing pregnant groups. Results: 435 patients were included in the study, in which 235 (58.8%) got clinical pregnancy, and 49 suffered miscarriage. Patients in both pregnant group and non-pregnant group, and miscarriage and ongoing pregnant group did not show significant difference in endometrial thickness, endometrial volume, endometrial pattern, uterine PI, RI, S/D, endometrial and subendometrial VI, FI and VFI. In relative thin endometrium group, pregnant patients had similar endometrial thickness, endometrial volume, endometrial pattern, uterine PI, RI, S/D, endometrial and subendometrial VI, FI and VFI with non-pregnant patients. Conclusion: 3D PDUS parameters of endometrium measured on hCG day were not good predictors of pregnancy in IVF treatment, neither good predictors of ongoing pregnancy.